Knowledge, Opinion and Practices; A Survey of National Coaches Regarding Diet Plan for Young Athletes in Pakistan (Journal of Asian Development Studies, 2023)
The study aimed to assess national coaches' knowledge, opinions, and practices regarding the perception of diet plans for young athletes in Pakistan. A sample of 45 national coaches was selected through a convenient sampling technique during Pakistan's 33rd National Games. The researchers developed a Likert-type scale for the collection of data from respondents. The collected data were analyzed through the SPSS 20.0 version. As a result of the data analysis, no significant difference was found among the respondents regarding knowledge of diet for young athletes (p-value was .079, which is > 0.05). No significant difference was found among the respondents regarding coaches' opinions about diet plans for young athletes (p-value was .091, which is > 0.05). No significant difference was found among the respondents regarding the current diet plan practice of young athletes (p-value was .086, which was > 0.05). Based on the analysis, the researchers recommend that the concerned authorities organize a diet awareness program and its role in sports performance.